Could Non-manufacturing Foreign Direct Investor Increase Productivity through Knowledge Transfer in Developing Countries? : A Chinese Case Study - Han, Wenxin (2007)
China 1.3 billion consumers and almost limitless supply of cheap labour attract foreign companies, which want to get a foothold in the Chinese market, to invest directly in the country. As a developing country, China used to face serious shortages of capital, management and technologies, which could be associated with foreign direct investment (FDI) that has been growing fast in the last few years in China, and is becoming a major component of foreign investment. Now, the huge inflow of foreign direct investment has enabled China becoming a world-manufacturing centre. In the past 15 years, China has attracted more foreign direct investment than any other developing country, and become the worlds third-largest recipient. On the other hand, the demand of the non-manufacturing foreign direct investment, especially the private equity funds that are also a new kind of FDI in China is increasing rapidly. By analyzing the data of some Chinese firms that got investment from a non-manufacturing foreign investor Dingyun who is doing FDI in China, this paper finds out that the non-manufacturing investors could develop the level of productivity of domestic firms by knowledge transfer, such as developing the human resource system, and then get the knowledge transfer from the experts who introduced by the private equity firm; providing the techniques that could develop the productivity; bringing the knowledge of overseas stock market that is important for the Chinese firms nowadays; moreover, the Chinese firm could receive some knowledge from operating with private equitys overseas network, thus improve the productivity. Finally, the new governance knowledge from the private equity firms could play an important role on developing productivity.